Emigration and Gravity Theory: Application on the Western Balkans - Malaj, Visar; Teka, Soana Jaupllari (European Journal of Multidisciplinary Studies, 2022)
The use of gravity equations for explaining international migration flows has significantly increased during the last years. The increased availability of data have allowed scholars to investigate numerous independent variables related to both the origin and the destination countries. The main objective of this study is the empirical investigation of Western Balkan emigration flows and some of the respective social and economic determinants. The region is both a migration source for developed EU countries, and a major migratory route for Asian and African migrants. We formulate and estimate different gravity equations for Western Balkan migrants. The considered explanators include shares of population with tertiary education, human development indexes as well as incomes per capita. Empirical results show a satisfactory explanatory power of the formulated models.
Keywords: International Migration, Gravity Theory, Western Balkans